2021
DOI: 10.3389/fonc.2020.595533
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA-PAICC Promotes the Tumorigenesis of Human Intrahepatic Cholangiocarcinoma by Increasing YAP1 Transcription

Abstract: Intrahepatic cholangiocarcinoma (ICC) is a heterogeneous hepatobiliary tumor with poor prognosis, and it lacks reliable prognostic biomarkers and effective therapeutic targets. Long non-coding RNAs (lncRNAs) have been documented to be involved in the progression of various cancers. However, the role of lncRNAs in ICC remains largely unknown. In the present work, we used bioinformatics analysis to identify the differentially expressed lncRNAs in human ICC tissues, among which lncRNA-PAICC was found to be an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Recent study demonstrated that lncRNA-PAICC was overexpressed in ICC tissues, and expression of PAICC enhanced proliferation and invasion of ICC cells [ 30 ]. Importantly, oncogenic PAICC functioned as competitive endogenous RNA (ceRNA) that adsorbed tumor-suppressive miRNAs, miR-141-3p and miR-27a-3p , in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study demonstrated that lncRNA-PAICC was overexpressed in ICC tissues, and expression of PAICC enhanced proliferation and invasion of ICC cells [ 30 ]. Importantly, oncogenic PAICC functioned as competitive endogenous RNA (ceRNA) that adsorbed tumor-suppressive miRNAs, miR-141-3p and miR-27a-3p , in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, oncogenic PAICC functioned as competitive endogenous RNA (ceRNA) that adsorbed tumor-suppressive miRNAs, miR-141-3p and miR-27a-3p , in cancer cells. Silencing of miR-141-3p and miR-27a-3p induced activation of the Hippo pathway in ICC cells [ 30 ]. Similarly, overexpression of lncRNA-UCA1 sponged miR-122 , and this event enhanced proliferation and invasion of ICC cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the lncRNA-related research has focused on the mechanism and function of dysregulated lncRNAs in the tissues and cells of CCA. The following lncRNAs have been documented to be linked to the prognosis of cholangiocarcinoma ( Table 2 ): ANRIL ( Angenard et al, 2019 ), ASAP1-IT1 ( Guo et al, 2018 ), CCAT1 ( Zhang et al, 2017a ), CCAT2 ( Xu et al, 2018a ), CRNDE ( Xia et al, 2018 ), FOXD2-AS1 ( Hu et al, 2022 ), GAPLINC ( Wang et al, 2018 ), H19 ( Xu et al, 2017a ), HOTAIR ( Qin et al, 2018 ), HOTTIP ( Gao et al, 2021 ), HOXD-AS1 ( Li et al, 2020b ), LINC00261 ( Gao et al, 2020 ), LINC00665 ( Lu et al, 2021 ), LINC00667 ( Li et al, 2021a ), LINC01296 ( Zhang et al, 2018a ), LOXL1-AS1 ( Zhang et al, 2019a ), NNT-AS1 ( Huang et al, 2019a ), MALAT1 ( Tan et al, 2017 ), PAICC ( Xia et al, 2020 ), PANDAR ( Xu et al, 2017b ), PCAT1 ( Sun et al, 2021 ), lnc-PKD2-2-3 ( Qiu et al, 2019 ), SNHG3 ( Tian et al, 2019 ), Sox2ot ( Li et al, 2018 ), TUG1 ( Xu et al, 2017c ), UCA1 ( Xu et al, 2017d ), ZEB1-AS1 ( Jiang et al, 2020a ), ZFAS1 ( Li et al, 2019c ).…”
Section: Lncrnas As Diagnostic and Prognostic Biomarkers In Cholangio...mentioning
confidence: 99%
“…Nowadays, several prognostic factors are identified to determine cholangiocarcinoma prognosis, including the ceRNA regulatory network (Xia et al, 2020) and DNA methylation (Nakaoka et al,FIGURE 4 | HCQ induces cell cycle arrest in the G1 phase of cholangiocarcinoma cells. (A) FCM analysis was used to detect cell cycle distribution after treatment with the IC50 concentration of HCQ, the histograms show the percentage of HuCCT-1 and CCLP-1 cells in the G1-S-G2 phase, and the comparison of G1 phase between two groups was analyzed using Student's t-test.…”
Section: Discussionmentioning
confidence: 99%